A Modified Map-Drift Algorithm for SAR Autofocusing - Wang, Wu; An, Daoxiang; Luo, Yuxiao; Zhou, Zhimin; Huang, Xiaotao (2018 Asia Pacific Microwave Conference (APMC), 2018)
Trajectory deviations in airborne synthetic aperture radar (SAR) will induce phase errors and degrade the quality of SAR images. For obtaining high resolution SAR images, motion compensation (MOCO) is performed by using the GPS or INS, furthermore, autofocusing algorithms should also be used for residual phase errors (RPE) correction. Map-Drift (MD), a commonly used SAR autofocusing algorithm, has the ability of correcting quadric phase errors (QPE) for improving the SAR imaging quality. In this paper, an improved MD algorithm is proposed. In the proposed method, principal component analysis (PCA) is adopted for fitting the linear equation between Doppler rate and range. Real-scenario experiment shows that the proposed method can provide more precise SAR imaging results compared with the conventional MD.